The Integration of Digital Technology in Islamic Education: Enhancing Learning Outcomes and Preserving Religious Values - Nur Rois; Nenden Munawaroh; Mahfud Ifendi; Arif Muzayin Shofwan; Galuh Nashrulloh Kartika MR (Eduprof : Islamic Education Journal, 2026)
The rapid advancement of digital technology has reshaped the global educational landscape, yet its adoption within Islamic education remains complex due to the unique emphasis on character cultivation and spiritual values. This study analyzes the integration of digital technology in Islamic education with a focus on how it enhances learning outcomes while preserving religious values. As education increasingly shifts towards digital platforms, Islamic education faces both opportunities and challenges in adopting modern tools without compromising its spiritual essence. This study employed a qualitative research design, utilizing semi-structured interviews with teachers, administrators, and students, alongside classroom observations and document analysis at madrasahs, pesantren, and Islamic universities. Participants were selected through purposive sampling to provide information-rich insights into technological implementation. The findings show that digital technology can facilitate interactive learning, expand access to educational resources, and improve students’ engagement. At the same time, it is crucial to safeguard Islamic values by carefully selecting and designing digital content that aligns with ethical and religious principles. Specific findings indicate that while gamification and multimedia tools improve comprehension in challenging subjects like Arabic grammar and fiqh, students face challenges such as digital distractions and exposure to unverified religious claims. The study highlights that when appropriately implemented, digital technology strengthens academic achievement and supports students’ holistic development in accordance with Islamic teachings. To ensure success, institutions must implement "Islamic digital citizenship" modules and curate online systems to maintain moral integrity. This integration serves as a strategic step in ensuring that Islamic education remains relevant, effective, and value-driven in the digital era.